Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s11661-020-05818-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrical Conductivity of Electrolytic Tough Pitch Copper Rods Processed by Incremental Equal Channel Angular Pressing

Abstract: Electrolytic tough pitch copper rods were processed by Incremental Equal Channel Angular Pressing and subjected to short-term annealing. Conductivity of 94 pct IACS without significant changes in the material’s microstructure and mechanical properties, up to 130 HV0.2, was achieved, which gives a very good ratio of electrical conductivity to strength in comparison with other processing methods. The proposed method offers a solution for manufacturing rods of significant sizes with good mechanical strength and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Kumar et al [35] explained the reduction of EC of the oxygen-free high conductivity Cu through cyclic channel die compression by increasing the density of deformation-induced defects such as point defect, dislocation density, and grain boundaries. A similar finding of decreasing the EC by increasing the number of passes was reported by Ko et al [36] for Cu-3 wt%Ag alloy and Wei et al [37] for pure Cu. On of contrary, Ciemiorek et al [38] reported the reduction of the Ec of Cu during the first pass while it revealed a subsequent increase as it processed through 8-passes.…”
Section: Electrical Conductivitysupporting
confidence: 85%
“…Kumar et al [35] explained the reduction of EC of the oxygen-free high conductivity Cu through cyclic channel die compression by increasing the density of deformation-induced defects such as point defect, dislocation density, and grain boundaries. A similar finding of decreasing the EC by increasing the number of passes was reported by Ko et al [36] for Cu-3 wt%Ag alloy and Wei et al [37] for pure Cu. On of contrary, Ciemiorek et al [38] reported the reduction of the Ec of Cu during the first pass while it revealed a subsequent increase as it processed through 8-passes.…”
Section: Electrical Conductivitysupporting
confidence: 85%
“…Research on the Cu-3 wt% Ag alloy and pure Cu by Ko et al [62] and Wei et al [54] further verified the previously documented drop in EC with the number of ECAP passes. However, Ciemiorek et al [72] discovered that after the first pass, the E C of Cu dropped, only for the E C to climb once again with the addition of subsequent passes until there were eight. Finally, Cho et al [73] studied the Cu-15Ag alloy and discovered that for 8-pass processing, the greatest E C values were obtained, in decreasing order, by routes C, A, and Bc.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…The electrical conductivity of UFG copper after 5 ECAP passes decreases by only 8% [23] and starts to increase slightly with subsequent passes [25], but never reaches the value of the initial material. In [29], it was proven that short-term annealing at low a temperature after ECAP processing results in relatively high electrical conductivity and while preserving the beneficial mechanical properties. These results indicate that ECAP processing makes it possible to manufacture a high-strength material whose electrical conductivity is only slightly lower than that of the initial, coarse-grained material.…”
Section: Introductionmentioning
confidence: 99%